Britain and the German Churches, 1945-1950 : the role of the Religious Affairs Branch in the British zone - Howson, Peter (Studies in modern British religious history, 2021)
Explores the ways in which the British Religious Affairs Branch aimed to organise religious life in post-war Germany.